Gastric inhibitory polypeptide receptor: association analyses for obesity of several polymorphisms in large study groups - Rief Winfried; Reinehr Thomas; Völzke Henry; Rosskopf Dieter; Bornhorst Alexa; Grallert Harald; Wang Hai-Jun; Nguyen Thuy T; Brönner Günter; Scherag André; Vogel Carla IG; Illig Thomas; et al. (BMC, 2009)
Abstract Background Gastric inhibitory polypeptide (GIP) is postulated to be involved in type 2 diabetes mellitus and obesity. It exerts its function through its receptor, GIPR. We genotyped three GIPR SNPs (rs8111428, rs2302382 and rs1800437) in German families with at least one obese index patient, two case-control studies and two cross-sectional population-based studies. Methods Genotyping was performed by MALDI-TOF, ARMS-PCR and RFLP. The family-study: 761 German families with at least one extremely obese child or adolescent (n = 1,041) and both parents (n = 1,522). Case-control study: (a) German obese children (n = 333) and (b) obese adults (n = 987) in comparison to 588 adult lean controls. The two cross-sectional population-based studies: KORA (n = 8,269) and SHIP (n = 4,310). Results We detected over-transmission of the A-allele of rs2302382 in the German families (pTDT-Test = 0.0089). In the combined case-control sample, we estimated an odd ratio of 1.54 (95%CI 1.09;2.19, pCA-Test = 0.014) for homozygotes of the rs2302382 A-allele compared to individuals with no A-allele. A similar trend was found in KORA where the rs2302382 A-allele led to an increase of 0.12 BMI units (p = 0.136). In SHIP, however, the A-allele of rs2302382 was estimated to contribute an average decrease of 0.27 BMI units (p-value = 0.031). Conclusion Our data suggest a potential relevance of GIPR variants for obesity. However, additional studies are warranted in light of the conflicting results obtained in one of the two population-based studies.